Inclusive charged hadron production in two-photon collisions at LEP - Dova, María Teresa (2003)
Inclusive charged hadron production, e+e− → e+e−h±X, is studied using 414 pb−1 of data collected at LEP with the L3 detector at centre-of-mass energies between 189 and 202 GeV. Single particle inclusive differential cross sections are measured as a function of the particle transverse momentum, pt , and pseudo-rapidity, η. For pt 1.5 GeV, the data are well described by an exponential, typical of soft hadronic processes. For higher pt , the onset of perturbative QCD processes is observed. The π± production cross section for pt > 5 GeV is much higher than the NLO QCD predictions.